2013
DOI: 10.1108/tr-09-2013-0055
|View full text |Cite
|
Sign up to set email alerts
|

Developing a brand structure pyramid model for travel-related online social networks

Abstract: 2013),"Developing a brand structure pyramid model for travel-related online social networks", Tourism Review, Vol. 68 Iss 4 pp. 49 -70 Permanent link to this document: http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 92 publications
(131 reference statements)
2
15
0
3
Order By: Relevance
“…People may travel for their annual vacation or for many other reasons such as: adventure, healthcare treatment, fun, culture, and to enjoy new experiences (Barreda et al, 2013, Nusair, 2008. Economically, the tourism sector is of growing importance to many countries.…”
Section: The Importance Of the Tourism Sector For Countriesmentioning
confidence: 99%
“…People may travel for their annual vacation or for many other reasons such as: adventure, healthcare treatment, fun, culture, and to enjoy new experiences (Barreda et al, 2013, Nusair, 2008. Economically, the tourism sector is of growing importance to many countries.…”
Section: The Importance Of the Tourism Sector For Countriesmentioning
confidence: 99%
“…Perasaan nyaman yang timbul ketika seseorang menggunakan suatu sistem akan berpengaruh terhadap perilaku selanjutnya (Venkatesh dan Davis, 2000;Venkatesh et al, 2003). Perceived enjoyment merupakan konstruk dimensional tunggal, dan dievaluasi dalam bentuk menyenangkan dan gembira dalam melakukan sebuah kegiatan (Wu dan Liu, 2007 Barreda et al (2013Barreda et al ( ) (2013. Instrumen tersebut dinilai dengan menggunakan skala likert 5 poin.…”
Section: Persepsi Menyenangkan (Perceived Enjoyment) Dan Niat Penggunaanunclassified
“…Penelitian ini merupakan pengembangan dari penelitian yang telah dilakukan Carter et al (2011) yaitu menggunakan tiga determinan utama model UTAUT (ekspektasi kinerja (performance expectancy), ekspektasi usaha(effort expectancy), pengaruh sosial (social influence)) dengan menambahkan faktor persepsi pribadi keyakinan diri dalam menggunakan web(web self efficacy), kontrol keamanan persepsian(perceived security control), dan persepsi menyenangkan (perceived enjoyment) yang dikembangkan oleh Barreda, Nusair, Okumus, dan Bilgihan (2013).Penelitian ini berusaha mengetahui apakah terdapat pengaruh ekspektasi kinerja (performance expectancy),ekspektasi usaha(effort expectancy), pengaruh sosial (social influence), keyakinan diri dalam menggunakan web(web self efficacy), kontrol keamanan persepsian(perceived security control), dan persepsi menyenangkan (perceived enjoyment) terhadap niat penggunaan approweb (Intention to Use Approweb).…”
unclassified
“…Dickinger and Mazanec [84] found that family recommendations and online reviews are the two factors that influence online hotel reservations the most. Travelers perceive information from social media as unbiased [85,86]. In fact, the vast majority of travelers use search engines and social networks when assessing a destination or tourist product [8].…”
Section: Social Network Community Usefulnessmentioning
confidence: 99%